Enhanced power-line energy harvesting by capacitance compensation for remote self-powered CO2 monitoring - Jieying Qian; Jiawen Xu (AIP Advances)
Aiming at carbon neutrality and compliance, it is necessary to monitor carbon emissions in remote areas. In this study, we proposed a remote self-powered CO2 monitoring system powered by a capacitance compensation enhanced power line energy harvester. The harvester consists of a magnetic core, a 4000-turn coil, and a matching capacitance. The coils would generate electrical energy due to the flux variation around the power lines. Besides, we demonstrate experimentally that the introduction of capacitance compensation would enhance the power output of the energy harvester and hence boost the overall efficiency of the system. Experimental studies of the proposed system revealed a capacitance compensation output power of 103.8 mW with a resistance load of 55 kΩ under 219 mArms current at 50 Hz. A microcontroller-based wireless sensor node was built for evaluation. The proposed system would ensure reliable remote CO2 monitoring mounted on power lines.